Mathematics
boo10bubba
4

How do I solve 4x + 3y=0 & 2x + y = -2 using substitution 

+0
(1) Answers
RickieCarnevale662

4x + 3y = 0 2x + y = -2 take 2x and subtract to the side with -2 it'll look like this: y = -2x - 2 plug that equation in where the y is in the other equation. it'll look like this: 4x + 3(-2x - 2)=0 which you multiply 3 and the -2x and the -2 which the equation would be: 4x - 6x - 6=0 put together like terms: -2x - 6=0 add the 6 to the side with the zero: -2x = 6 divide both sides by -2 which x= -3 to get y you plug in the answer for x (-3) 2(-3)+y= -2 so it'd then be -6 + y = -2 add the -6 to the side with -2 y= -2 +6 y= 4 so your complete answer is ( -3, 4)

Add answer